CONCEPTUALIZATION OF SHARIA-BASED FAMILY EDUCATION TOWARDS AN ISLAMIC FAMILY IN THE ERA OF GLOBALIZATION - Rambe, Khairul Mufti; Saprijal, Saprijal; Lubis, Amru Syahputra; Harahap, Mursal (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
Background: The family is the main base of Islamic education that supplies the first educational material for students. The low knowledge of sharia will cause a serious gap in the practice of Islamic teachings in the current era of globalization. Purpose of the research: is to find out the conceptualization of sharia-based family education towards Islamic families in the era of globalization, to find out the purpose of the concept of sharia-based family education, and to find out the practical strategies of sharia-based family education towards Islamic families in the era of globalization. Methods: this study uses a qualitative approach, with primary and secondary literature as the main source of research. Results: this shows that the concept of sharia-based family education aims to create the character of students who have high spiritual values, uphold aspects of monotheism, justice and law, as well as nobility of heart that has the value of patience and gratitude for all forms faced in life. The conceptualization strategy of sharia-based family education can be implemented through the internalization of Islamic values, including sharia-based character education, role empowerment in accordance with sharia, sharia financial education, Islamic child education, parental involvement in education, wise use of technology, and flexible approaches to social change. Conclusions: Knowing the concept of sharia-based family education in the era of globalization is very important in caring, maintaining, developing and the potential of students in the family sphere in order to create an Islamic personality in the midst of the globalization era.